2011
DOI: 10.1590/s1983-51752011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sildenafil and buflomedil on survival of randomized flaps in rats: an experimental study

Abstract: Figueiredo JCA et al. Influence of sildenafil and buflomedil on survival of randomized flaps in rats: an experimental study Influência do buflomedil e do sildenafil na sobrevivência de retalhos randomizados em ratos: estudo experimental ABSTRACT Background: Microcirculation dysfunction, as a consequence of localized vascular insufficiency, is considered to be one of the dominant causes of surgical flap necrosis. Several vasoactive drugs have been tested for the pharmacological treatment of tissue ischemia, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This finding was in harmony with the results of Kaya et al 43 , Sarifakioglu et al 44 , Tsai et al 45 and Shah et al 8 who used sildenafil also as a treatment and concluded that sildenafil is able to improve skin flap survival in a dose-dependent manner. In contrast, Figueiredo et al 46 , Barral et al 47 , Serin et al 4 and Ayyildiz et al 11 had revealed that sildenafil does not affect skin viability. These negative data shown by those authors for sildenafil treatment may be due to the different doses or the different routes of administration that were used.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was in harmony with the results of Kaya et al 43 , Sarifakioglu et al 44 , Tsai et al 45 and Shah et al 8 who used sildenafil also as a treatment and concluded that sildenafil is able to improve skin flap survival in a dose-dependent manner. In contrast, Figueiredo et al 46 , Barral et al 47 , Serin et al 4 and Ayyildiz et al 11 had revealed that sildenafil does not affect skin viability. These negative data shown by those authors for sildenafil treatment may be due to the different doses or the different routes of administration that were used.…”
Section: Discussionmentioning
confidence: 94%